QUO VADIS POLITIK PEREMPUAN? - Sumiarti Sumiarti (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
To what direction Indonesian women politic will be? Is it aim correctly to give opportunity to women to participate in state’s social-politic process, or only as politicizing effort to women? Is state policy to women could affect society mindset in viewing and positioning women in order to equal with man? Woman politic in Indonesia absolutely must have purpose to empower woman and on broader scale to improve social order to became more gender justice. Woman involvement in public area, should not only fulfill formal requisite to obligation to involve woman, but really based on consideration about important role played by woman on public domain. Therefore, it will not emerge effort and activity that only politicizing woman